Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.22271/ortho.2018.v4.i1a.06
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on patients with road traffic accidents admitted in department of orthopaedics at a rural hospital in India (a retrospective study of more than 1000 patients)

Abstract: Background &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Similar findings were observed in a study done by Aditya et al in Vadodara and Khan SP, Hussain AR in Tirupati who found that most common age group affected was 21-30 years (34.91%& 34.20% respectively). 23,24 This is because the youths are the one often having been involved risk taking behaviour and increased usage of vehicle for college, work and other purposes. This is indicating the loss of tender; active and productive age people are the one affected by RTA related injuries in turn adding to higher economic loss to the country.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were observed in a study done by Aditya et al in Vadodara and Khan SP, Hussain AR in Tirupati who found that most common age group affected was 21-30 years (34.91%& 34.20% respectively). 23,24 This is because the youths are the one often having been involved risk taking behaviour and increased usage of vehicle for college, work and other purposes. This is indicating the loss of tender; active and productive age people are the one affected by RTA related injuries in turn adding to higher economic loss to the country.…”
Section: Resultsmentioning
confidence: 99%
“…8 As per a study, most of the victims of RTAs are the breadwinner of the family. 9 The financial burden, particularly, is high for poorer households in rural areas, and those seeking treatment at private health facilities with no health insurance. 10 RTAs continue to be a social threat, incurring a heavy loss of valuable human resource.…”
Section: Introductionmentioning
confidence: 99%